2010
DOI: 10.1007/s00233-010-9273-7
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatisability problems for S-posets

Abstract: Let C be a class of algebras of a given fixed type τ . Associated with the type is a first order language L τ . One can then ask the question, when is the class C axiomatisable by sentences of L τ ? In this paper we will be considering axiomatisability problems for classes of left S-posets over a pomonoid S (that is, a monoid S equipped with a partial order compatible with the binary operation). We aim to determine the pomonoids S such that certain categorically defined classes are axiomatisable. The classes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We present here a more general procedure to axiomatise these classes. A similar type of general results have been found for S-posets by Gould and Shaheen [10]. We have found that there are some classes of S-acts which are axiomatisable by more than one method.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…We present here a more general procedure to axiomatise these classes. A similar type of general results have been found for S-posets by Gould and Shaheen [10]. We have found that there are some classes of S-acts which are axiomatisable by more than one method.…”
supporting
confidence: 87%
“…We denote the class of C-flat left S-act by CF . Note: for S-posets there will be two variations of the notion of C-flat, as we explain in [10].…”
Section: General Results On Axiomatisabilitymentioning
confidence: 99%
See 3 more Smart Citations